Dampak Transformasi Digital pada Agribisnis: Tantangan dan Peluang bagi Petani di Indonesia - Lokot Muda Harahap; Tiarasi Gloria Pakpahan; Ratri Aulia Wijaya; Ahmad Zacky Nasution (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Digital transformation has brought significant impact to the agriculture sector in Indonesia by improving operational efficiency, opening new market opportunities, and introducing the concept of digital farming and agriculture 4.0. Although the government has encouraged agricultural digitalization through policies and programs, farmers still face challenges such as land limitations, climate change, and limited market access. Collaboration between the government, private sector, and non-profit organizations is needed to support farmers' adoption of digital technologies to improve their efficiency, productivity, and welfare. Challenges such as lack of internet access, low digital literacy, and high technology implementation costs also need to be addressed through cross-sector collaboration. This research highlights the importance of synergy in capitalizing on digital opportunities and overcoming barriers in the digital transformation of Indonesia's agriculture sector.